Is your client rich? someone will be looking over your shoulder. - Linthicum, David S. (SOA webservices journal.)
As we look to make more practical use of Web services, the need has emerged for a better user interface; one that's neither too fat nor too thin. An interface that allows developers to make the most out of the client's native features, while at the same time, not bogging the client down with services that are better kept at the back end.